2022
DOI: 10.1101/2022.05.18.22275184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerated Aging Mediates the Associations of Unhealthy Lifestyles with Cardiovascular Disease, Cancer, and Mortality: Two Large Prospective Cohort Studies

Abstract: With a well-validated aging measure – Phenotypic Age Acceleration (PhenoAgeAccel), this study examined whether and to what extent aging mediates the associations of unhealthy lifestyles with adverse health outcomes. Data were from 405,944 adults (40-69 years) from UK Biobank (UKB) and 9,972 adults (20-84 years) from US National Health and Nutrition Examination Surveys (NHANES). The mediation proportion of PhenoAgeAccel in associations of unhealthy lifestyles with incident cardiovascular disease, incident cance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Numerous previous studies have revealed the longitudinal evolution of physical and mental ability in the elderly population, highlighting the fact that abilities of the elderly gradually decline over time. However, it is not just a simple linear relationship [45]. Over time, many of the abilities of the elderly population will decline more rapidly, and the impact of such a decline will gradually increase [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have revealed the longitudinal evolution of physical and mental ability in the elderly population, highlighting the fact that abilities of the elderly gradually decline over time. However, it is not just a simple linear relationship [45]. Over time, many of the abilities of the elderly population will decline more rapidly, and the impact of such a decline will gradually increase [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…α-Klotho is an anti-aging protein primarily produced in the kidneys [ 7 , 8 , 9 ]. A previous study has shown that Phenotypic Age Acceleration, a measure of accelerated aging, partially mediates the association of unhealthy lifestyles, including an unhealthy diet, with adverse health outcomes, such as cardiovascular disease, cancer, and mortality, in populations from the UK and the US [ 33 ]. Our findings suggest an anti-aging mechanism underlying the relationship between a healthy diet and enhanced kidney function through the involvement of serum α-Klotho, which plays a crucial role in preserving kidney health by regulating calcium and phosphate metabolisms, inhibiting renal fibrosis, reducing oxidative stress, and promoting anti-inflammatory effects [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the above equation, CA represents the chronological age; x represents the value of biomarker j; q, k, and s represent parameters when biomarker j is regressed on CA; and sBA represents a scaling factor equal to the square root of the variance in chronological age explained by the biomarker set. Furthermore, we calculated the BioAgeAccel (20) by estimating the differences in the biological and chronological age (21). A negative BioAgeAccel value indicated a lower biological age.…”
Section: Measurement Of Biological Agementioning
confidence: 99%